2006
DOI: 10.1111/j.1600-0838.2006.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, bone mass and bone size in prepubertal boys: one‐year data from the pediatric osteoporosis prevention study

Abstract: This non-randomized prospective controlled study evaluates a daily school-based exercise intervention program of 40 min/school day for 1 year in a population-based cohort of 81 boys aged 7-9 years. Controls were 57 age-matched boys assigned to the general school curriculum of 60 min/week. Bone mineral content (BMC; g) and areal bone mineral density (aBMD; g/cm(2)) were measured with dual X-ray absorptiometry (DXA) of the total body, the third lumbar vertebra (L3) and the femoral neck (FN). Bone width for L3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(116 citation statements)
references
References 44 publications
6
108
1
1
Order By: Relevance
“…On review of these trials an additional seven trials were identified and added to those being reviewed [8,29,38,42,43,49,55] (Table 1). Of these trials, 14 were excluded because of duplication of study populations (Table 1), and one did not present measures of variance for changes in bone outcomes [8].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…On review of these trials an additional seven trials were identified and added to those being reviewed [8,29,38,42,43,49,55] (Table 1). Of these trials, 14 were excluded because of duplication of study populations (Table 1), and one did not present measures of variance for changes in bone outcomes [8].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…1 The flowchart shows the numbers of articles initially identified and exclusion and inclusion steps. * Randomization unit: I = individual, S = school or class; D = change; These studies provided different data from the same study: Löfgren et al [31] was used for female and male total body, femoral neck, and spine BMC; Linden et al [29] was used for male femoral neck BMD; Valdimarsson et al [50] was used for female spine and femoral neck BMD; NS = not stated; DPA = dual photon absorptiometry, DXA=dual energy x-ray absorptiometry; pQCT = peripheral quantitative computed tomography; BMC = bone mineral content; BA = bone area; aBMD = areal bone mineral density; PHV = peak height velocity; PF = proximal femur; LS = lumbar spine; FN = femoral neck; TB = total body; FA = forearm; TR = trochanter; PC = periosteal circumference; EC = endosteal circumference; Ar = area; CortAr = cortical area; CortThk = cortical thickness; Cort = cortical; Tot = total; vBMD = volumetric bone mineral density; MSCA = muscle crosssectional area; AS!BC = Action Schools! British Columbia.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…Body weight was measured with the subjects lightly dressed to the nearest 0.1 kg using an electronic scale (Seca 882). Bicipital, tricipital, subscapular and suprailiac skinfolds were measured with a Harpenden skinfold calliper in the children by two experienced scientists according to conventional criteria and measuring procedures (22). A questionnaire used to report gender and physical activity during school breaks, active transport and playing outside in leisure time was completed by 586 children at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…In fact the gains demonstrated in Fuchs et al (2001) were greater than those in the MacKelvie et al (2001MacKelvie et al ( , 2001) studies, most likely due to the larger ground reaction forces generated (8.8 vs. 3.5-5 x body weight). Studies at 12 months (Alwis et al, 2008b;Linden et al, 2007) utilizing a weight bearing physical education intervention follow a similar trend with improvements being seen in boys but not girls. The extra intervention time has not helped to elicit a significant positive bone response in the young girls.…”
Section: Prepubertal Interventionsmentioning
confidence: 58%
“…It would therefore appear that improvements in bone as a result of a PA intervention would more likely occur in prepubertal boys than girls. This is particularly true after 7 months of jumping training (MacKelvie et al, 2001 and 12 months of weight bearing PA (Alwis et al, 2008b;Linden et al, 2007). Improvements in prepubertal girls were seen in studies lasting 24 months in duration ) and any studies demonstrating bone gains in a mixed gendered population (Fuchs et al, 2001;McKay et al, 2000) could be due to greater changes in the boys than the girls.…”
Section: Prepubertal Interventionsmentioning
confidence: 95%